Examining the role of instructional materials in the implementation of history 2166 syllabus in Zimbabwe - Sengai, Walter; Mokhele, Matseliso L. (African Perspectives of Research in Teaching & Learning, 2021)
Teachers’ capacities to effectively deliver in the classroom can be strengthened if they have more access to instructional resources which facilitate the grasping of concepts by learners. The scarcity of instructional materials worsened by insufficient financial resources to fund the initiatives spelt the doom of earlier curriculum reforms. This paper used a phenomenological design to qualitatively explore the perceptions of History teachers on the role of instructional resources in the implementation of the History 2166 syllabus reform in Zimbabwe. The paper looks at the availability, use and impact of instructional resources on the instructional process during the implementation of the new syllabus. Five History teachers drawn from five secondary schools in the Glen View/ Mufakose district in the Harare Metropolitan province were purposively sampled. The participants were interviewed using semi-structured interviews which were audio tapped, transcribed, coded and categorised into the major themes on the role of instructional materials in the implementation of the History 2166 syllabus reforms. Findings from this study show that the scarcity ofinstructional resources played a part in making the teaching of the History 2166 syllabus almost an insurmountable feat. However, teachers had the obligation to be resourceful and innovative in order to ensure that learners were exposed to the best possible instructional practices. The apparent lack of the necessary instructional materials significantly contributed to the challenges encountered by the History 2166 syllabus which culminated in its withdrawal from the History classroom in 2000. This study concludes that instructional resources are a key factor in curriculum reform since the extent of their availability determines the success or failure of the implementation of a new syllabus. Key words: History 2166 syllabus; implementation; instructional materials; syllabus reform
Article published in the African Perspectives of Research in Teaching & Learning (APORTAL) Vol 5(1): 2021
Keywords: History 2166 syllabus; Implementation; Instructional materials; Syllabus reform; Classroom learning centers; Curriculum change